Wireless Sensor Network for Radiation Detection - Suliman Abdel Rahman Abdalla (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2017)
In this paper a wireless sensor network (WSN) is designed from a group of radiation detector stations with different types of sensors. These stations are located in different areas and each sensor transmits its data through GSM network to the main monitoring and control station. The design includes GPS module to determine the location of mobile and fixed station.  The data is transmitted with GSM/GPRS modem. Instead of using traditional SMS data string or word messages a digital data frame is constructed and transmitted as SMS data. In the main monitoring station graphical user interface (GUI) software is designed to shows information and statues of the all stations in the network. It reports any radiation leaks, in addition to the data; the GUI contains a geographical map to display the location of the leakage station and can control the stations power consumption by sending a special command to it.